فاعلية برامج قبعات التفكير الست في تنمية بعض مهارات التفكير الابتكاري لدى تلاميذ الصف الرابع الأساس - محمد الشامي, سهى (Al-Adab Journal, 2018)
Title Search: The Effectiveness of the Six Thinking Hats strategy in the development of some innovative thinking skills for Basic fourth–Grade Pupils. The goal of current research to reveal the effectiveness of the strategy of the Six Thinking Hats in the development of some of the skills of innovative thinking skills for Basic fourth–Grade Pupils, and to achieve the objectives of the research approach was used quasi-experimental-based Measurement ( pre/post ) was used as a strategy Six Thinking Hats and the application of the Torrance Test of thinking innovative (photocopy b) and applied to a sample of children of Basic fourth –Grade Pupils in Homs, amounted to (50) pupils and using the test "T" to analyze the data given to the research found the following results:1-There are significant differences at the level of significance (0.05) between the mean scores of the experimental group and the control group in the skill of flexibility in dimensional measurement.2-There were statistically significant differences at the level of significance (0.05) between the mean scores of the experimental group and the control group in the skill of originality in dimensional